Stimulation of Eryptosis by Combretastatin A4 Phosphate Disodium (CA4P) - Elena Signoretto; Rosi Bissinger; Michela Castagna; Florian Lang (Cellular Physiology and Biochemistry, 2016)
Background/Aims: Combretastatin A4 phosphate disodium (CA4P) is utilized for the treatment of malignancy. The substance has previously been shown to trigger suicidal cell death or apoptosis. Similar to apoptosis of nucleated cells, erythrocytes may enter suicidal death or eryptosis, characterized by cell shrinkage and cell membrane scrambling with phosphatidylserine translocation to the erythrocyte surface. Stimulators of eryptosis include increase of cytosolic Ca2+ activity ([Ca2+]i), ceramide, oxidative stress and ATP depletion. The present study explored, whether CA4P induces eryptosis and, if so, to gain insight into mechanisms involved. Methods: Flow cytometry has been employed to estimate phosphatidylserine exposure at the cell surface from annexin-V-binding, cell volume from forward scatter, [Ca2+]i from Fluo3-fluorescence, reactive oxygen species (ROS) abundance from DCF fluorescence, glutathione (GSH) abundance from CMF fluorescence and ceramide abundance from fluorescent antibodies. In addition cytosolic ATP levels were quantified utilizing a luciferin-luciferase-based assay and hemolysis was estimated from hemoglobin concentration in the supernatant. Results: A 48 hours exposure of human erythrocytes to CA4P (≥ 50 µM) significantly increased the percentage of annexin-V-binding cells and significantly decreased forward scatter. CA4P did not appreciably increase hemolysis. Hundred µM CA4P significantly increased Fluo3-fluorescence. The effect of CA4P (100 µM) on annexin-V-binding was significantly blunted, but not abolished, by removal of extracellular Ca2+. CA4P (≥ 50 µM) significantly decreased GSH abundance and ATP levels but did not significantly increase ROS or ceramide. Conclusions: CA4P triggers cell shrinkage and phospholipid scrambling of the erythrocyte cell membrane, an effect at least in part due to entry of extracellular Ca2+ and energy depletion.